Mediating role of job satisfaction in the relationship between organizational identification and organizational commitment : an empirical study on ship agency employees - Yorulmaz, Murat (Array, 2020)
Understanding the relationship between an organization and the employees in that organization is of paramount importance for the success and future of that organization. This is related to the measurement of the organizational attitudes and behaviours of employees and the use of these attitudes and behaviours for forward-looking predictions. This being said, the aim of the study is to explore the relationship between the organizational identification levels of employees in ship agencies, and their job satisfaction and organizational commitment. For the purpose of this study, the data were obtained from 265 employees of different ship agencies in the cities of Istanbul and Kocaeli, Turkey, through questionnaire. The data then were analyzed via the structural equation modeling analyses, which were conducted using AMOS v22 by Bootstrap resampling with 5000 replications; the results have showed that organizational identification has both a positive direct and an indirect effect on organizational commitment, the latter through job satisfaction. Further, this study revealed that organizational identification, together with job satisfaction, explained about 0.59% of the variation in organizational commitment.